Influence of Synthetic Antioxidants Used in Food Technology on the Bioavailability and Metabolism of Lipids - In Vitro Studies - Magdalena Mika; Anna Antończyk; Agnieszka Wikiera (Polish Journal of Food and Nutrition Sciences, 2023)
Synthetic antioxidants, such as butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), and tert-butylhydroquinone (TBHQ), have been widely used for many years to stabilise lipids in foods. Nonetheless, their effect on the bioavailability and metabolism of lipids stabilised with them still remains unknown. To investigate this issue, in vitro digestion of a model high-fat product (20 g fat/100 g) without antioxidants and supplemented with BHT, BHA and TBHQ (100 mg/kg) was conducted, followed by studies using the Caco-2 and Hep G2 cell lines. BHT, BHA and TBHQ increased intestinal absorption of triacylglycerols and modified the structure of chylomicrons (CM). The addition of BHT and TBHQ inhibited apolipoprotein-IV (apoA-IV) synthesis. At the same time, smaller chylomicrons were secreted, but their amount was greater than in the model product without antioxidants. In contrast, BHA activated apoA-IV synthesis, resulting in the formation of fewer but very large CMs. Of concern was the significant decrease in apoA-IV in cells upon the use of BHT and TBHQ, which can lead to obesity due to the lack of the sensation of feeling full after eating high-fat foods stabilised with these antioxidants. Furthermore, the efficiency of CM remnant (CMR) uptake by hepatocytes was inversely correlated with their size. The large CMRs generated for samples with BHA were not absorbed by hepatocytes, which can lead to atherosclerosis. The results of our in vitro study shed new light on the role of synthetic phenolic antioxidants used in food technology as potential obesity and atherosclerosis triggers and suggested the need for further research that will clearly separate antioxidants that promote the development of these diseases from those, which do not do that.